2010
DOI: 10.1097/hco.0b013e32833f0236
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo assessment of the natural history of coronary atherosclerosis: vascular remodeling and endothelial shear stress determine the complexity of atherosclerotic disease progression

Abstract: The dynamic interplay between the local hemodynamic environment and the wall remodeling behavior determines the complexity of the natural history of atherosclerosis and explains the development of localized plaque vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 77 publications
1
13
1
2
Order By: Relevance
“…Some studies have demonstrated that high shear stress may be related to plaque rupture. [23][24][25] It is hoped that the research on assessing this WSS distribution near the plaque will accurately discover plaque rupture positions. Unfortunately, in-vivo evidence of such a relation is limited because the Hagen-Poiseuille equation cannot be applied to Copyright: American Scientific Publishers assess WSS near plaque as the geometry of vessels with plaque is irregular and the blood flow direction may change.…”
Section: Regional Wss Distribution Surroundingmentioning
confidence: 99%
“…Some studies have demonstrated that high shear stress may be related to plaque rupture. [23][24][25] It is hoped that the research on assessing this WSS distribution near the plaque will accurately discover plaque rupture positions. Unfortunately, in-vivo evidence of such a relation is limited because the Hagen-Poiseuille equation cannot be applied to Copyright: American Scientific Publishers assess WSS near plaque as the geometry of vessels with plaque is irregular and the blood flow direction may change.…”
Section: Regional Wss Distribution Surroundingmentioning
confidence: 99%
“…The abnormal proliferation of SMCs expresses abundant collagen, especially in the development and progression of CVD, and forms a thickly and elastic fibrous cap over a core of lipids, inflammatory and necrotic cells [40]. Cys C is a member of the cystatin superfamily of endogenous cysteine protease inhibitor and which can inhibit the degradation of ECM [41]. The ECM of the vessel wall is composed of collagen, elastin, proteoglycans and a number of other glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…28,53 This forms a necrotic core with recruitment of smooth muscle cells from the media to seal over the fatty core. 15 Flow-induced WSS is now well established as being a critical determinant of the specific sites at which this intra-wall process develops, 11,65 explaining in part its focal nature given that the same serum courses throughout the vascular system. In addition to local fluid mechanical differences, there are also solid mechanical variances that are contributory.…”
Section: Processes Influencing Coronary Plaque Sitementioning
confidence: 99%